Kantian Criticism: Reinterpreting Epistemology for the Transformation of Sharia Economics - Munir, Akhmad Sirojudin; Achmad Khudori Soleh (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2024)
This study identifies the development of sharia economic epistemology, particularly in terms of the lack of integration of Western epistemological theories, especially Kantian epistemology, into the framework of sharia economics. The purpose of this study is to explore how the reinterpretation of Kantian epistemology can enrich the theory and practice of sharia economics, as well as identify the potential for methodological improvements in sharia economic research. The research method used is qualitative design with a literature study approach and conceptual analysis, which involves thematic and content analysis of relevant academic literature. The results show that the integration of Kantian epistemology can provide a new dimension in sharia economic theory by introducing a priori category and cognitive structure, as well as improving research methodologies with a more reflective and holistic approach. The application of the Kantian principle can also improve sharia economic practices in the global market and support the formation of more adaptive policies. Recommendations for further research include empirical testing of the application of Kantian epistemology in various sectors of the sharia economy, as well as the development of a policy framework based on Kantian principles to improve flexibility and responsiveness to global changes.